The Effect of Progressive Muscle Relaxation Using Classical Music on the Recovery of Soccer Players - Darusalam, Rijal Malik; Komarudin, Komarudin; Febrianty, Mona F. (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This study aims to determine the effect of progressive muscle relaxation method using classical music and classical music relaxation method on the recovery of soccer players. The method used in this research is an experiment with two group pretest-posttes design. The sampling technique in this study used total sampling technique. The sample in this study were members of PS Bina Pakuan (age 16-17) totaling 20 members. The instrument in this study used a polar H10 device to measure pulse / minute. Data analysis used Shapiro-Wilk test, Levene Statistics, Paired Sample T-Test, and Independent Sample T-Test with the help of SPSS 29 application. Based on data processing and analysis it was found that: 1) Progressive muscle relaxation method using classical music has a significant effect on the recovery of soccer players, 2) The classical music relaxation method has a significant effect on the recovery of soccer players, and 3) There is a significant difference in effect between progressive muscle relaxation method using classical music and classical music relaxation method.